A prática pedagógica da professora de piano Glenda Romero: Um estudo de caso - Leandro, Lindberg Luiz da Silva (2015)
This research aimed to observe the pedagogical practice of the piano teacher Glenda Romero with two students in João Pessoa/PB, focusing on her decisions, reflected in her actions and in the way as she conduct the classes. Also interested to note aspects related to teaching and learning, as the choice of teaching resources used, the musical practice through the piano, motivation and centralization of education. Being a qualitative research, this case study was conducted by collecting data, participant observation, notebook diary, recording audio/video and semi-structured interviews with all participants. Data analysis brought reflections on the practice of private piano teaching by Glenda Romero, considering its actions throughout the process of teaching and learning. We realize that she used teaching materials in a reflective way, she was flexible with the student regarding the re-reading the score during class, teaching was centered in their teaching behavior and, among other conclusions, the main purpose of the lessons included encouraging the reading of sheet music and musical practice at the piano.